Exit strategies and state building - Caplan, Richard (Richard D.) (New York : Oxford University Press, 2012)
This volume provides a comparative study of exit with regard to international operations of a state-building nature. The essays focus on the empirical experiences of, and scholarly and policy questions associated with, exit in relation to four families of experience: colonial administrations, peace support operations, international territorial administrations, and transformative military occupations.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Nation-building -- Case studies; Peace-building -- Case studies